2022
DOI: 10.1002/chem.202202102
|View full text |Cite
|
Sign up to set email alerts
|

Free Aluminylenes: An Emerging Class of Compounds

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Further reactivity explorations reveal that the Al( i ) center of compound 5 exhibits ambiphilicity (Scheme 3). 31 Compound 5 readily engages in oxidation reactions 106 with IDippCuCl or (THT)AuCl and cycloaddition reactions 110 with unsaturated hydrocarbons, yielding the respective aluminium (di)chloride products 5-P1 to 5-P2 and aluminium heterocycles 5-P3 to 5-P5 . More recently, reactivity of compound 5 towards boron Lewis acids has been explored, giving diverse aluminum–boron-bonded species 5-P6 to 5-P7 .…”
Section: Group 13 Carbene Analogues (B Al Ga In and Tl)mentioning
confidence: 99%
See 2 more Smart Citations
“…Further reactivity explorations reveal that the Al( i ) center of compound 5 exhibits ambiphilicity (Scheme 3). 31 Compound 5 readily engages in oxidation reactions 106 with IDippCuCl or (THT)AuCl and cycloaddition reactions 110 with unsaturated hydrocarbons, yielding the respective aluminium (di)chloride products 5-P1 to 5-P2 and aluminium heterocycles 5-P3 to 5-P5 . More recently, reactivity of compound 5 towards boron Lewis acids has been explored, giving diverse aluminum–boron-bonded species 5-P6 to 5-P7 .…”
Section: Group 13 Carbene Analogues (B Al Ga In and Tl)mentioning
confidence: 99%
“…27 The carbene analogues mentioned above possess an electron configuration with a lone pair of electrons and a formally unoccupied p-orbital. 25,28–31 The stable versions of these analogues often exhibit a closed-shell singlet ground state. In stark contrast, their triplet variants are typically unstable, and have been primarily documented through gas-phase studies or spectroscopic means.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this process initially resulted in formal B–F oxidative addition and formation of a borylfluoroaluminate ( 11 ), the highly reactive tetraorganoalumaborane ( 12 ) could be liberated by treatment with Me 3 SiOTf. Even more recently, Zhang and Liu have reported that, although unreactive toward BPh 3 , treatment of the carbazolyl aluminylene ( 13 ) with Ph 2 BOBPh 2 proceeds by B–OC oxidative addition at the Al­(I) center to provide the (boryloxy)­(boryl)­alumane ( 14 ). , In this contribution, we extend this mode of reactivity to B–O oxidative addition through the reaction of 8 with readily available cyclic and acyclic borate esters. We also describe an initial assay of the reactivity of the resultant (boryl)­(alkoxy)­aluminates with heteroallenes and the transformation of a dimethoxyboryl derivative to a terminal alumaboronic ester featuring trigonal N 2 Al-BO 2 coordination environments at both boron and aluminum.…”
Section: Introductionmentioning
confidence: 94%
“…Even more recently, Zhang and Liu have reported that, although unreactive toward BPh 3 , treatment of the carbazolyl aluminylene ( 13 ) with Ph 2 BOBPh 2 proceeds by B–OC oxidative addition at the Al(I) center to provide the (boryloxy)(boryl)alumane ( 14 ). 57 , 58 In this contribution, we extend this mode of reactivity to B–O oxidative addition through the reaction of 8 with readily available cyclic and acyclic borate esters. We also describe an initial assay of the reactivity of the resultant (boryl)(alkoxy)aluminates with heteroallenes and the transformation of a dimethoxyboryl derivative to a terminal alumaboronic ester featuring trigonal N 2 Al-BO 2 coordination environments at both boron and aluminum.…”
Section: Introductionmentioning
confidence: 99%